Brønsted Acid Mediated Direct α-Hydroxylation of Cyclic α-Branched Ketones - Shevchenko, Grigory A.; Dehn, Stefanie; List, Benjamin (Synlett, 2018)
We report a Brønsted acid mediated direct α-hydroxylation of cyclic α-branched ketones via a tandem aminoxylation/N–O bond-cleavage process. Nitrosobenzene is used as the oxidant and subsequently promotes the liberation of the free alcohol. The desired products could be isolated in moderate to good yields at a maximum tested scale of 10 mmol. Derivatizations of the obtained products are presented.
Keywords: α-branched ketones; α-hydroxylation; aminoxylation; α-functionalization of ketones; enolization; Brønsted acid mediated